Portal fibroblasts with mesenchymal stem cell features form a reservoir of proliferative myofibroblasts in liver fibrosis. Issue 5 (29th March 2022) - Lei, Lin; Bruneau, Alix; El Mourabit, Haquima; Guégan, Justine; Folseraas, Trine; Lemoinne, Sara; Karlsen, Tom Hemming; Hoareau, Bénédicte; Morichon, Romain; Gonzalez‐Sanchez, Ester; Goumard, Claire; Ratziu, Vlad; et al.
Abstract: Background and Aims: In liver fibrosis, myofibroblasts derive from HSCs and as yet undefined mesenchymal cells. We aimed to identify portal mesenchymal progenitors of myofibroblasts. Approach and Results: Portal mesenchymal cells were isolated from mouse bilio‐vascular tree and analyzed by single‐cell RNA‐sequencing. Thereby, we uncovered the landscape of portal mesenchymal cells in homeostatic mouse liver. Trajectory analysis enabled inferring a small cell population further defined by surface markers used to isolate it. This population consisted of portal fibroblasts with mesenchymal stem cell features (PMSCs), i.e., high clonogenicity and trilineage differentiation potential, that generated proliferative myofibroblasts, contrasting with nonproliferative HSC‐derived myofibroblasts (‐MF). Using bulk RNA‐sequencing, we built oligogene signatures of the two cell populations that remained discriminant across myofibroblastic differentiation. SLIT2, a prototypical gene of PMSC/PMSC‐MF signature, mediated profibrotic and angiogenic effects of these cells, which conditioned medium promoted HSC survival and endothelial cell tubulogenesis. Using PMSC/PMSC‐MF 7‐gene signature and slit guidance ligand 2 fluorescent in situ hybridization, we showed that PMSCs display a perivascular portal distribution in homeostatic liver and largely expand with fibrosis progression, contributing to the myofibroblast populations that form fibrotic septa, preferentially along neovessels, in murine and human liver disorders, irrespective of etiology. We also unraveled a 6‐gene expression signature of HSCs/HSC‐MFs that did not vary in these disorders, consistent with their low proliferation rate. Conclusions: PMSCs form a small reservoir of expansive myofibroblasts, which, in interaction with neovessels and HSC‐MFs that mainly arise through differentiation from a preexisting pool, underlie the formation of fibrotic septa in all types of liver diseases. Abstract :